The Phenomenon of Indonglish Usage at Tidar University: Breaching the Motives from Sociolinguistics Perspectives - Riadil, Ikrar Genidal; Nur, Muhammad Rauuf Oktavian (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
The aim of this study was to analyze the specific vocabulary in the Indonglish phenomenon that the Tidar University students use in the educational environment at Tidar University, the meaning that exists in Indonglish at Tidar University, and the impact of Indonglish usage in the use of Indonesian is good and right in the environment education in universities at Tidar University in a signification effort Indonesian. Indonglish is a term often used for English language which is nuanced by Indonesian culture. Indonglish study focuses on environmental education, particularly in higher education that is not only limited to the academic setting but also non-academic one. The researchers used qualitative research. The data of this research were a wide range of speeches acquired in an educational environment, especially in Java, in which there are forms of language linguistically mixed Indonesian and English. Locational data source of this research were the perpetrators of students at Tidar University. The result is the 5th semester students produced 35 Indonglish vocabulary and the 7th semester students produced 31 Indonglish vocabulary. The basic assumption for determining the locational data sources was the consideration that the students, faculties, and staff had a varied background of social, economic and culture so that it was expected to describe the condition of society. The data analysis was conducted by applying the distributional method that was commonly done in linguistics. The method of analysis was done after the data were collected and properly classified. Furthermore, the interpretation of the data was done. Then, the interpreted data were presented informally.